The effectiveness of iodine supplementation during pregnancies in geographical areas of high prevalence of iodine insufficiency - Mallika Vongchana (2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. The objective of this study was to determine the effectiveness of routine iodine supplementation among pregnant women in areas of high prevalence of an iodine insufficiency, using WHO criteria to determine the iodine status. A longitudinal study was conducted on pregnant women attending antenatal care at a tertiary hospital. The urine iodine concentration was measured in the first trimester and after 150 μg of iodine supplementation in the third trimester. A total of 327 pregnant women met the inclusion criteria with a complete follow-up. The prevalence of an iodine insufficiency was significantly lower in the third trimester, when compared to the first trimester (21.41% vs 55.35%, p <.001). However, 21.4% of cases still had an iodine insufficiency and 35.17% had an ‘above-requirement’ in the third trimester. In the areas of high prevalence of iodine insufficiency, an iodine supplementation significantly reduces the number of women with insufficiency; however, it was associated with unnecessarily high UICs, leading to the risk of excess iodine.Impact statementWhat is already known on this subject: Iodine insufficiency is highly prevalent in many geographical areas. Half of the pregnant women in the northern part of Thailand had an iodine insufficiency in the first trimester. What do the results of this study add: Iodine supplementation (daily 150-mcg of potassium iodide) could significantly reduce the number of women with the insufficiency. About one-fifth of women still had an iodine insufficiency in spite of iodine supplementation. Universal supplementation could be associated with unnecessarily high UICs, potentially at risk of iodine excess. What are the implications of these findings for clinical practice and/or further research: Physicians should guard against the occurrence of adverse effect from an iodine excess when there is routine iodine supplementation for pregnant women. Further study is required to establish the best strategy for an iodine supplementation in pregnancy.